Evaluating trade and economic relations between India and Southeast Asia - Medhekar, Anita, 1962- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book investigates the trade and economic linkages between India and Southeast Asia, covering aspects of business, trade and commerce in an attempt to benefit stakeholders to understand the opportunities and challenges while strengthening the cultural ties to each other"--